PENGARUH PENGETAHUAN INVESTASI, KEMAJUAN TEKNOLOGI, DAN DAYA DUKUNG KAMPUS TERHADAP MINAT INVESTASI - Musa, Fernanda Bagas; Sundari, Siti (International Journal of Multidisciplinary Research and Literature, 2024)
This study examined the effect of investment knowledge, technological progress, and campus support capacity on student investment interest. The subjects in this study were accounting students at the National Development University "Veteran" East Java class of 2019-2022, which has a population of 1,158 students. Simple random sampling obtained a sample of 92 respondents. Data collection using questionnaires distributed by Google Forms. Technical analysis using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach through the SmartPLS 3.0 software application. The results of this study indicate that the better investment knowledge students have will likely encourage student investment interest. Meanwhile, technological progress in the investment process has not been able to increase the investment interest of UPN "Veteran" East Java Accounting students. Campus support in the form of investment management and investment law courses and other facilities can increase student interest in investment